Energy‐aware supply route data collecting methods using wireless sensor networks. Issue 8 (29th January 2015) - Huang, Shih‐Chang; Chang, Hong‐Yi
Abstract: In military action, marching is a common method used for supply‐troop movement. Supply routes are typically in the wilderness where the route conditions change over time. This paper proposes a power‐saving algorithm allowing supply troops to collect route information using wireless sensor network technology. Each member in the marching supply troop is equipped with a battery‐powered sensor. To save power consumption, the proposed methods schedule the sleeping period for each member according to the size of the marching supply troop and its moving velocity. Two data carrying methods are proposed to reduce the frequency of long‐distance data uploading. The first method allows the uploaded data to be carried within a single‐round data collection period, and the second method extends the data carrying period to multiple rounds. The simulation results show that scheduling a sleep period can prolong the sensing distance along the route. These two proposed methods can add an additional 18–70% in distance data over methods without scheduling a sleep period. The energy spent on long‐distance data transmissions can be improved by 7–25%. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In military action, marching is a common method used for supply‐troop movement. This paper proposes a power‐saving algorithm allowing supply troops to collect route information using wireless sensor network technology. Two data carrying methods are proposed to reduce the frequency of long‐distance data uploading. The simulation results show that sensing distance along the route can be prolonged and the energy spent on long‐distance data transmission can save 7–25%.